Manahil al-Irfan fi Ulum al-Quran - Az-Zarqani, Muhammad 'Abd al-Azim (Abdallaelanady, 2020)
This book is part of the contemporary pearls, it regroups practically all the sciences of the Quran in a remarkable style and organization. This is a book that is full of knowledge encompassing 17 chapters of the Qur'an and its sciences such as the causes of revelation, types of suras, the various readings, history gathering the Koran, the order that he knows, Tafseer and Mufassirun, translation, abrogated verses, its miraculous kind etc.